Molecular pathogenesis of Hodgkin's lymphoma: increasing evidence of the importance of the microenvironment - Steidl, Christian; Connors, Joseph M; Gascoyne, Randy D (Journal of clinical oncology, 2011)
Hodgkin's lymphoma (HL) represents the most common subtype of malignant lymphoma in young people in the Western world. Most patients can be cured with modern treatment strategies, although approximately 20% will die after relapse or progressive disease. The histologic hallmark of the disease is the presence of the characteristic Hodgkin Reed-Sternberg (HRS) cells in classical HL and so-called lymphocyte-predominant (LP) cells in nodular lymphocyte-predominant HL. HL is unique among all cancers because malignant cells are greatly outnumbered by reactive cells in the tumor microenvironment and make up only approximately 1% of the tumor. Expression of a variety of cytokines and chemokines by the HRS and LP cells is believed to be the driving force for an abnormal immune response, perpetuated by additional factors secreted by reactive cells in the microenvironment that help maintain the inflammatory milieu. The malignant HRS and LP cells manipulate the microenvironment, permitting them to develop their malignant phenotype fully and evade host immune attack. Gene expression signatures derived from non-neoplastic cells correlate well with response to initial and subsequent therapies, reflecting their functional relevance. Recent biomarker studies have added texture to clinical outcome predictors, and their incorporation into prognostic models may improve our understanding of the biologic correlates of treatment failure. Moreover, recent preclinical and clinical studies have demonstrated that the tumor microenvironment represents a promising therapeutic target, raising hope that novel treatment strategies focused on the interface between malignant and reactive cells will soon emerge.